Karakteristik Tapak Tegakan Hutan Mangrove (Rhizophora mucronata dan Avicennia marina) di Pantai Kelurahan Bira Kecamatan Tamalanrea Kota Makassar - Budirman Bachtiar; Resti Ura'; Suhartati Suhartati (Universitas Hasanuddin, 2023)
Mangrove forests help protect coastlines from abrasion and provide organic matter from the stands. Mangrove species have special abilities to adapt to extreme environmental conditions, such as flooded soil conditions, high salt content and unstable soil conditions. This study aims to determine the characteristics of mangrove forest stands (Rhizophora mucronata and Avicennia marina) in Pantai Kelurahan Bira, Tamalanrea District, Makassar City. This research was conducted by analyzing the characteristics of the mangrove stands of Rhizophora mucronata and Avicennia marina species consisting of texture, color, pH, carbon, organic matter, nitrogen, phosphorus, potassium content, silt depth and soil salinity. The results showed that the texture of the soil was classified as clay, clayey clay and dusty clay. The soil color is brownish black and the soil pH is neutral. Organic matter has a high to excessive category, soil Nitrogen and Phosphorus levels are classified as low to moderate, and Potassium levels are classified as moderate. The average soil depth is 67.72 cm (medium) and the salinity consists of belonging to the high category with an average value of 26.48 ms.